(ICORG 05-03): prospective randomized non-inferiority phase III trial comparing two radiation schedules in malignant spinal cord compression (not proceeding with surgical decompression); the quality of life analysis. (3rd July 2018) - Lee, K. A.; Dunne, M.; Small, C.; Kelly, P. J.; McArdle, O.; O'Sullivan, J.; Hacking, D.; Pomeroy, M.; Armstrong, J.; Moriarty, M.; Clayton-Lea, A.; Parker, I.; et al.
Abstract: Background: The optimal primary external beam radiation therapy (EBRT) radiation schedule for malignant epidural spinal cord compression (MSCC) remains to be determined. The ICORG 05-03 trial assessed if a 10 Gy single fraction radiation schedule was not inferior to one with 20 Gray (Gy) in five daily fractions, in terms of functional motor outcome, for the treatment of MSCC in patients not proceeding with surgical decompression. This article reports on two of the secondary endpoints, Quality of life (QoL), assessed according to the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core 30 (QLQ-C30) version 3.0 (EORTC Data Center, Brussels, Belgium) and pain control assessed using a visual analog scale. Methods: A randomized, parallel group, multicenter phase III trial was conducted by Cancer Trials Ireland (formerly All-Ireland Cooperative Oncology Research Group, ICORG), across five hospital sites in Ireland and Northern Ireland. Patients were randomized to 10 Gy single fraction of EBRT or 20 Gy in five fractions in a 1:1 ratio. Patients with baseline and 5-week follow up QoL data are included in this analysis. Findings: From 2006 to 2014, 112 eligible patients were enrolled for whom 57 were evaluated for this secondary analysis. After adjusting for pre-intervention scores, there was no statistically significant difference in post-treatment Summary scores (excl. FI and QL), or pain scores between the two RT schedules at 5 weeks and 3 months following EBRT. There was a statistically significant relationship between the pretreatment and post-treatment Summary scores ( p  =  .002) but not between the pre-treatment and post-treatment pain scores. Interpretation: Primary radiotherapy for the treatment of MSCC significantly improves QoL in patients not proceeding with surgical decompression. After adjusting for pre-intervention scores, there was no statistically significant difference between a 10 Gy single fraction radiation schedule and one with 20 Gy in five daily fractions on post-treatment QoL Summary scores. For most patients, an effective treatment with low burden would be desirable. A single fraction schedule should be considered for this group of patients.